Committee on Veterans Affairs, House of Representatives. (U.S. Congressional Research., 1953)
Veterans Administration report on H.R. 1438, to authorize the Administrator of Veterans Affairs to furnish space and facilities to representatives of certain recognized state organizations; cites similar bill from previous Congress.